Generally, I am stumped by the Phi function. I have found out the pattern but I am having difficulty proving it. 1. The problem statement, all variables and given/known data i) When p is a prime number, obtain an expression in terms of p for:- ϕ(p²) 2. Relevant equations ϕ(p)=p-1 3. The attempt at a solution ϕ(p)=p-1 so ϕ(5)=4 therefore p²=5²=25 therefore ϕ(p²)=20 Also, if p=3 then ϕ(3)=2 therefore ϕ(9)=6 It appears that ϕ(p²)= p(p-1) My problem is that I am not able to proof it. Yes, the pattern is p(p-1) but I am stuck as to how to explain it. Any soloutions?